The Portuguese law on Surrogacy – Promises and Perils - Araújo, Marisa Almeida (Frontiers in Law, 2023)
After years of intense debate, on August 22, 2016 the Portuguese Assisted Reproductive Technologies (ART) Law was altered, and altruistic gestational surrogacy was made legal in Portugal. Although the journey has not been easy since then. The Portuguese Constitutional Court was called twice (in 2018 and 2019) to analyse the legal provisions of the surrogacy legal regime. The judges concluded that altruistic surrogacy was not in violation of the Portuguese Constitution, although the legal solution, and later amendment, was, in some of its provisions, unconstitutional. The judges found that the law needed to guarantee the right of the surrogate to regret the arrangement after the child was born. Considering the rulings of the Constitutional Court, surrogacy contracts in Portugal are not enforceable and the surrogate can, after the child is born, revoke her consent and become the legal mother of the child. The Parliament altered the Law accordingly in 2021, although, for the time being, it is still to be regulated. Using qualitative methods, including legal, and bioethical analyses and a review of literature, this paper introduces an overview of the Portuguese legal solution on surrogacy and discusses, in particular, the right to regret of the surrogate after the child is born. The conclusion is that the Portuguese law on surrogacy does not yet have a clear and needed position about who are, in fact, the parents or mother(s) of the child in contested surrogacy contracts if the surrogate regrets the arrangement and revokes her consent after the child is born.